Logging and Log Interpretation - Evaluation of Porosity Derivation from Neutron Logs - R. H. Widmyer; G. M. Wood (The American Institute of Mining, Metallurgical, and Petroleum Engineers)
This investigation was prompted by the absence of a simple, accurate method to predict optimum second stage separation pressure in three stage separation operations. Three stage separation as used here includes two separators plus the stock tank. The first stage pressure is usually fixed by gas sales conditions and the third stage is at atmospheric pressure. Thus, the second stage pressure is the only one that may be varied in-discriminantly during production operations. No variations in temperature were considered in this study, even though it will vary among systems, for a change in temperature has little effect on the optimum pressure. Optimum pressures may be determined from flash calculations, but these are tedious unless a computer is available. An early attempt to develop a simpler method' yielded an equation which gave the optimum pressure only as a function of initial and final pressure. Experience, however, confirms theoretical relationships which show that composition as well as pressure and temperature must be a factor. This indicates that the basic relationship should be an equation of the form, where P, is second stage pressure, P, is first stage pressure, A is a function of P. (stock-tank pressure) and the system composition, and n is a function of the number of stages and the system composition. Fig. 1 shows the basic variation of P2 with P for a fixed system composition. A series of such figures clearly showed the effect of composition. The peak of each curve reflects that second stage pressure at which the stock-tank recovery (gal/MMcf) residue gas is a maximum value. DEVELOPMENT OF NEW CORRELATION Wellstreams having 17 different analyses, ranging from low gravity crude to condensate, were used to determine the effect of composition. Each wellstream was flashed through three stages to determine the optimum second stage pressure for each first stage pressure. Equilibrium vaporization ratios proposed by Latham and Campbell were used throughout. The heptane plus fraction, for simplicity, was assumed to have the properties of octane. The results were subjected to an empirical analysis in an attempt to develop a correlation- that would be (1) simple, (2) accurate, and (3) eliminate the need for any flash vaporization calculations. This analysis yielded two equations, one for wellstreams having a specific gravity greater than one (air = 1.0) and one for those less than one. For crude streams (specific gravFor condensate (specific gravity < 1.0),